Fungsi Peredaman UPFC pada Sistem Tenaga Listrik Mesin Tunggal Bus Tak Berhingga - Sasongko Pramono Hadi; Wijaya Yudha Atmaja; Rahmad Syahputra Lubis (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
The usual configuration of a UPFC consists of two voltage source converters, which are connected through a common DC link capacitor. One converter is connected in shunt and the other is in series to transmission line in a substation. UPFC is normally located on a transmission network requiring reactive power, with the primary duty to be power flow control. The secondary function could be transient stability improvement due to their rapid response. This research aims to investigate the dumping function of UPFC in coordination with Power Oscillation Damping (POD) Controller in Single Machine Infinite Bus (SIMB) with Power System Stabilizer (PSS). The presence of UPFC in the existing system equipped with both conventional controller and PSS in the generator, could lead to get a dynamics and stability system improvement, a precise adjustment of these controller parameter of POD has been carried out in order to get a good and appropriate set of parameter value.